2016
DOI: 10.12659/msm.898440
|View full text |Cite
|
Sign up to set email alerts
|

Donor Safety in Adult-Adult Living Donor Liver Transplantation: A Single-Center Experience of 356 Cases

Abstract: BackgroundAs an important means to tackle the worldwide shortage of liver grafts, adult-adult living donor liver transplantation (A-ALDLT) is the most massive operation a healthy person could undergo, so donor safety is of prime importance. However, most previous research focused on recipients, while complications in donors have not been fully described or investigated.Material/MethodsTo investigate donor safety in terms of postoperative complications, the clinical data of 356 A-ALDLT donors in our center from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…The volume of the liver graft should be determined to ensure the absolute safety of the donor but also to meet the need of the recipient. Insufficient RLV has been reported to be a major risk factor for donor mortality and morbidity . The RLV should be no less than 30%‐35% of the initial whole liver volume according to the International Liver Transplantation Society Guidelines .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of the liver graft should be determined to ensure the absolute safety of the donor but also to meet the need of the recipient. Insufficient RLV has been reported to be a major risk factor for donor mortality and morbidity . The RLV should be no less than 30%‐35% of the initial whole liver volume according to the International Liver Transplantation Society Guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient RLV has been reported to be a major risk factor for donor mortality and morbidity. (24)(25)(26) The RLV should be no less than 30%-35% of the initial whole liver volume according to the International Liver Transplantation Society Guidelines. (9) However, Kim et al reported that there was no significant difference in overall complication between RLV < 30% and RLV 30% in liver donor with a preserved middle hepatic vein (MHV), age < 50 years, and no or mild fatty changes.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, morbidity ranges between 17% and 40% in most analyses. [18][19][20][21][22][23][24][25][26][27] Major complications appear in 2% to 13% of cases. This is in line with the findings of the present analysis where we found a 36% complication rate, with most of these patients having minor complications and approximately 5% of all patients having major (grade II) complications.…”
Section: Discussionmentioning
confidence: 99%
“…(16,24) The findings enabled the understanding that when greater patient involvement is obtained in the manipulation of medications, a greater level of treatment adherence is achieved, leading to an improvement in the patient's clinical condition, reducing infection rates, re-admission, and graft rejection. (12,(21)(22)(23) Category 2 -Culture of patient safety in the transplant units The category presents questions related to the safety culture of patients undergoing renal, (18,19) hepatic, (11) abdominal, (24) pancreatic, (20) and bone marrow transplantation, (14) in the pre-and intra-operative periods.…”
Section: Presentation Of the Categoriesmentioning
confidence: 99%
“…With regard to the prevention of possible irregularities and complications, it was noted that the use of prophylactic antibiotics, as well as biopsies, was strategies that could minimize the risk of infections and prevent other health events, such as early rejection. (11,19,20)…”
Section: Presentation Of the Categoriesmentioning
confidence: 99%